Knowledge Transfer from Science to Technology—The Case of Nano Medical Device Technologies - Wang, Lili; Li, Zexia (Frontiers in Research Metrics and Analytics, 2018)
This study explores to what extent scientific knowledge has contributed to the development of industrial technologies. Backward citation is used to track the contribution of scientific research to technologies, and forward citation is adopted to evaluate the impact of these technologies. Patents are classified in two different groups (citing and not citing scientific publications) and a special attention has been given to the comparisons between countries, different types of organizations and different sub-fields. Our result reveals that, in the field of nano medical device technologies, knowledge transfer from the academic domain to the industrial domain is on the rise. The forward citations received by science-based patents are 1.6 times higher than those received by non-science-based patents. Our results also show that interconnections between science and technology are especially important for patents invented by firms compared to those developed by universities. At country level, all the six studied countries (U.S., Germany, U.K., Japan, France and China) have been applying more and more scientific knowledge to develop nano medical device technologies. The linkage between science and technology is strongest in the U.S. while it is weakest in the latecomer country China.